The Chemical Composition and Biological Properties of Coconut (Cocos nucifera L.) Water - Yan Fei Ng; Swee Ngin Tan; Jean W. H. Yong; Liya Ge (Molecules, 2009)
Coconut water (coconut liquid endosperm), with its many applications, is one of the world’s most versatile natural product. This refreshing beverage is consumed worldwide as it is nutritious and beneficial for health. There is increasing scientific evidence that supports the role of coconut water in health and medicinal applications. Coconut water is traditionally used as a growth supplement in plant tissue culture/micropropagation. The wide applications of coconut water can be justified by its unique chemical composition of sugars, vitamins, minerals, amino acids and phytohormones. This review attempts to summarise and evaluate the chemical composition and biological properties of coconut water.